Traffic flow forecasting model - Andziulienė, Beatričė; Stanelytė, Daiva; Drungilas, Darius (Lietuvos matematikos rinkinys, 2012)
The paper presents a mathematical model based on multicriteria decision making method of the Analytic Hierarchy Process for determining the critical network of railway lines, which prevented the flow of traffic growth, the line bandwidth, traffic volume and train speed. The presented model using real data and expert evaluation can be used for the renovation work schedules of railway lines (infrastructure, telecommunications, etc.).
Keywords: railway system; multicriteria decision making; AHP; traffic flow